Development and validation of a nomogram predictive model for cognitive impairment in cerebral small vessel disease: a comprehensive retrospective analysis - Li, Ning; Gao, Yan; Li, Li-tao; Hu, Ya-dong; Ling, Li; Jia, Nan; Chen, Ya-jing; Meng, Ya-nan; Jiang, Ye (Frontiers in Neurology, 2024)
Background Cerebral small vessel disease (CSVD) is a common neurodegenerative condition in the elderly, closely associated with cognitive impairment. Early identification of individuals with CSVD who are at a higher risk of developing cognitive impairment is crucial for timely intervention and improving patient outcomes. Objective The aim of this study is to construct a predictive model utilizing LASSO regression and binary logistic regression, with the objective of precisely forecasting the risk of cognitive impairment in patients with CSVD. Methods The study utilized LASSO regression for feature selection and logistic regression for model construction in a cohort of CSVD patients. The model’s validity was assessed through calibration curves and decision curve analysis (DCA). Results A nomogram was developed to predict cognitive impairment, incorporating hypertension, CSVD burden, apolipoprotein A1 (ApoA1) levels, and age. The model exhibited high accuracy with AUC values of 0.866 and 0.852 for the training and validation sets, respectively. Calibration curves confirmed the model’s reliability, and DCA highlighted its clinical utility. The model’s sensitivity and specificity were 75.3 and 79.7% for the training set, and 76.9 and 74.0% for the validation set. Conclusion This study successfully demonstrates the application of machine learning in developing a reliable predictive model for cognitive impairment in CSVD. The model’s high accuracy and robust predictive capability provide a crucial tool for the early detection and intervention of cognitive impairment in patients with CSVD, potentially improving outcomes for this specific condition.